Lost in Transformation: Rediscovering LLM-Generated Campaigns in Social Media - Grimme, Britta; Pohl, Janina; Winkelmann, Hendrik; Stampe, Lucas; Grimme, Christian (Disinformation in Open Online Media: 5th Multidisciplinary International Symposium, MISDOOM 2023, Amsterdam, The Netherlands, November 21–22, 2023, Proceedings)
This paper addresses new challenges of detecting campaigns in social media, which emerged with the rise of Large Language Models (LLMs). LLMs particularly challenge algorithms focused on the temporal analysis of topical clusters. Simple similarity measures can no longer capture and map campaigns that were previously broadly similar in content. Herein, we analyze whether the classification of messages over time can be profitably used to rediscover poorly detectable campaigns at the content level. Thus, we evaluate classical classifiers and a new method based on siamese neural networks. Our results show that campaigns can be detected despite the limited reliability of the classifiers as long as they are based on a large amount of simultaneously spread artificial content.
Keywords: Social Media; Campaign Detection; Large Language Models; Siamese Neural Networks

Informal Street Vending in Harare - Bhila, Ishmael; Chiwenga, Edson (Interventions)

Bist du eine Hauptfigur, eine Nebenfigur oder nur ein Outtake und nie im Bilde in deinem Leben? Sophie Linnenbaums Filme als Korrespondenz zwischen Film- und realen Welten - Keuchen, Marion (theo mag . tà katoptrizómena – Magazin für Kunst| Kultur | Theologie | Ästhetik. Filmische Passionen)

Polarization in Online Social Networks: A Review of Mechanisms and Dimensions - Tölle, Laura; Trier, Matthias

A Social Network Approach for Investigating Social Influences on Effective Use: Demonstration in Virtual Reality Collaboration - Tölle, Laura; Slawinski, Elena; Fromm, Jennifer; Mirbabaie, Milad

Spectral correspondences for rank one locally symmetric spaces - The case of exceptional parameters - Hilgert, Joachim; Arends, C. (J. de l'École polytechnique — Mathématiques)

Aspects of control theory on infinite-dimensional Lie groups and G-manifolds - Hilgert, Joachim; Glöckner, H. (J. Diff. Equations)

Autonomous Golf Putting with Data-Driven and Physics-Based Methods - Junker, Annika; Fittkau, Niklas; Timmermann, Julia; Trächtler, Ansgar (2022 Sixth IEEE International Conference on Robotic Computing (IRC))

CFD-Untersuchungen der Fluiddynamik und des Wärmetransports an rauen Oberflächen - Hollenhorst, Viola; Kenig, Eugeny Y.

Intraoperative Monitoring of Visuospatial and Linguistic Skills: Scenario Description for a More Standardised Practice - Tampier, Carla; Keil, Phillip; Becker, Maura; Jonas, Kristina; Goldbrunner, Roland; Lucas, Carolin Weiss (Brain and Spine)

Textilien (Herstellung, Verarbeitung, Handel) - Droß-Krüpe, Kerstin (RAC)

Ex India rediens hic fuit - Dokumentarische Quellen zu den Akteuren im römischen Rotmeerhandel von Augustus bis in die severische Zeit - Droß-Krüpe, Kerstin (Trade and Seafaring in Antiquity: Red Sea - Persian Gulf - Indian Ocean. Proceedings of the 1st Muziris Workshop, Trier, 28th May 2021)

Vertrag statt Vertrauen? Überlegungen zur Lehrlingsausbildung im frühkaiserzeitlichen Ägypten - Droß-Krüpe, Kerstin (Vertrauen als ökonomische Ressource in der antiken Marktwirtschaft)

Not Paying Taxes in Roman Egypt - Droß-Krüpe, Kerstin (Histories of Tax Evasion, Avoidance and Resistance)

Changing Identities at the Turn of the Common Era: The Case of Semiramis - Droß-Krüpe, Kerstin (Studia Orientalia Electronica)

Trade and Seafaring in Antiquity: Red Sea - Persian Gulf - Indian Ocean. Proceedings of the 1st Muziris Workshop Trier, 28th May 2021,

Orientalist Gazes. Reception and Construction of Images of the Ancient Near East since the 17th Century

#bedürfnisorientiert und #bindungsorientiert. Ein Erziehungstrend in den Sozialen Medien - Menzel, Tessa-Marie (Sozial Extra)

Theorielose Empirie? Ideen zu einem theoretisch sensibilisierten Forschen mit der Grounded Theory - Menzel, Tessa-Marie; Equit, Claudia (Qualitatives Forschen in der Erziehungswissenschaft. Prozesse und Vielfalt der rekonstruktiven Erkenntnisgewinnung)

When Do Firms Highlight Their Effective Tax Rate? - Flagmeier, Vanessa; Müller, Jens; Sureth-Sloane, Caren (Accounting and Business Research)
This study examines GAAP effective tax rate (ETR) visibility as a distinct disclosure choice in firms’ financial statements. By applying a game-theory disclosure model for the voluntary disclosure strategies of firms, in a tax setting, we argue that firms face a trade-off in their ETR disclosure decisions. On the one hand, firms have an incentive to enhance their ETR disclosure when the ratio offers shareholders ‘favourable conditions’, for example, higher expected after-tax cash flows. On the other hand, the disclosure of a favourable low ETR could attract the attention of tax auditors and the public and ultimately result in disclosure costs. We empirically test disclosure behaviour by examining the relation between disclosure visibility and different ETR conditions that reflect different stakeholder-specific costs and benefits. While we find that unfavourable ETR conditions are not highlighted, we observe higher disclosure visibility for favourable ETRs (smooth, close to the industry average, and decreasing ETRs). Additional analyses reveal that this high visibility is characteristic of firm years with only moderately decreasing ETRs at usual ETR levels, while extreme ETRs are not highlighted. Interestingly and in contrast to our main results, a subsample of family firms does not seem to highlight favourable ETRs.